Perceived health status and self‑esteem in relation to health‑related quality of life among adolescents living in orphanages: a multi‑institutional study - Ispriantari, Aloysia; Agustina, Rismia; Auwalu Ibrahim, Zainab (Jurnal Ners, 2026)
Introduction: Health-related quality of life (HRQoL) reflects the physical, mental, and social well-being of adolescents. Individuals in orphanages are often exposed to stress, which may undermine their HRQoL. This study aimed to explore the HRQoL of adolescents living in orphanages and to examine the roles of perceived health status, self-efficacy, and demographic factors. Methods: A multi-center cross sectional study with convenience sampling was conducted to recruit 238 adolescents aged 13-18 years from 16 orphanages in Malang City, Indonesia. Data were obtained using the KIDSCREEN-27 Child and Adolescent Version, Perceived Health Status, and Rosenberg Self-Esteem Questionnaires. Stata 16.0 was used to conduct descriptive statistics, Pearson correlations, and hierarchical linear regressions. Results: The mean total HRQoL score was 94.4±12.7, with the highest sub‑scale score in peers and social support (3.8±0.7) and the lowest in physical well-being (3.2±0.7). Perceived health status (8.9±1.8) and self-esteem (29.1±3.5) were both positively associated with HRQoL (r=0.31 and r=0.48, respectively; p<0.001), whereas the two variables were not correlated with each other (r=0.09, p>0.05). In the parsimonious regression model, perceived health status (β=3.19, p<0.001) and self-esteem (β=0.97, p<0.001) together explained 30% (R²=0.30) of the variance in HRQoL; inclusion of demographic characteristics increased the explained variance to only 31% and none reached statistical significance. Conclusions: These findings suggest that perceived health status and self-esteem are determinants of HRQoL in adolescents living in orphanages. Nurses should prioritize routine assessments and implement interventions that strengthen self-esteem and perceived health status to improve HRQoL among adolescents living in orphanages.